The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00330-006-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

MDCT urography: retrospective determination of optimal delay time after intravenous contrast administration

Abstract: The optimal delay time after intravenous (i.v.) administration of contrast medium (CM) for opacification of the upper urinary tract (UUT) for multidetector computed tomography urography (MDCTU) was investigated. UUT opacification was retrospectively evaluated in 36 four-row MDCTU examinations. Single- (n=10) or dual-phase (n=26) MDCTU was performed with at least 5-min delay after i.v. CM. UUT was divided into four sections: intrarenal collecting system (IRCS), proximal, middle and distal ureter. Two independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…If a corticomedullary phase is employed, data acquisition is usually started 25-35 s after start of CM injection [9,22]. The nephrographic phase starts after a delay of 90-110 s after start of the CM injection [9,23,28,30,32,33,37], while for the final excretory phase a fixed delay of 240-480 s after the start of CM injection has been used [9,[28][29][30]32]. In more recent times, excretory phase data acquisition has been further delayed to 720 s for improved depiction of the lower ureter [38].…”
Section: Intravenous Injection Of CMmentioning
confidence: 99%
See 1 more Smart Citation
“…If a corticomedullary phase is employed, data acquisition is usually started 25-35 s after start of CM injection [9,22]. The nephrographic phase starts after a delay of 90-110 s after start of the CM injection [9,23,28,30,32,33,37], while for the final excretory phase a fixed delay of 240-480 s after the start of CM injection has been used [9,[28][29][30]32]. In more recent times, excretory phase data acquisition has been further delayed to 720 s for improved depiction of the lower ureter [38].…”
Section: Intravenous Injection Of CMmentioning
confidence: 99%
“…Single-bolus CM injections use 100-150 ml of nonionic CM (300-370 mgI/ml) injected at a rate of 2-3 ml/s [9,22,23,[28][29][30][31][32][33][34][35][36][37]. If a corticomedullary phase is employed, data acquisition is usually started 25-35 s after start of CM injection [9,22].…”
Section: Intravenous Injection Of CMmentioning
confidence: 99%
“…It has previously been shown that delay time for CTU in the excretory phase after i.v.administration of contrast media is crucial for the proportion of urinary tract segments completely delineated, particularly for the distal ureter [5][6][7]. Delay time for the excretory phase exceeded 10 min in most patients, which is usually associated with increased success at delineating the ureter [3,[5][6][7]. Ancillary manoeurvres were restricted to the i.v.…”
Section: Discussionmentioning
confidence: 99%
“…hydration of the patient, i.v. administration of low doses of frusemide prior to CTU [6][7][8], and obtaining additional CT images in the excretory phase [9]. However, one major concern in CTU is additional radiation exposure due to (repetitive) CT data acquisitions in the excretory phase [3,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation